Silagem de bagaço de laranja pré-seco na alimentação de cordeiros - Valença, Roberta de Lima (2013)
This trial was composed of two experiments. In the first the objective of was ascertain this chemical characteristics of theof the silage of orange bagasse pre-dried ( SOB ) as well as this fermentative characteristics at different storage times. In the second experiment the objective was to determine the effect of replacement of maize by sob, in the of Santa Inês lambs and cost benefit of the diets. In the first experiment was conduced in laboratorial PVC mini silo with 10 cm diameter and 70 cm long, with a capacity of about 10 kg which are sealed with a lid equipped with a valve PVC "Bunsen" type. Adopted a distributed in a completely randomized design with five treatments and six replications . The treatments were different opening times of mini silos in days (10, 20, 40, 60 and 80). It was determined the chemical and fermentation parameters . The values of DM, CP , NDF , lignin and TDN did not suffer influence of opening days . The pre - drying increased the dry matter content of 28.3 % . Reduction in the ADF and increase in MM to advance the days of ensiling . The pH decreased during the days of storage , since the values of ammonia nitrogen did not vary . The values for dry matter losses and gases decreased after 60 days of storage , since the RMS did not change in relation to treatments . The orange peel can be stored efficiently in preserving their nutrients over the form of silage. According to the results found in this work silage orange has good nutritional value . In the second experiment 20 lambs with approximately 150 days of age and average weight (BW ) of 25 kg were fed for 73 days or until they reached 35 kg, fed diets with increasing levels of SBL replacing corn ( 0 , 33 , 66 and 100 % DM ) . There was a decline in dry matter intake (DMI) in g / day and% PV that showed average values of 914.62 g / day and 2.75 % BW respectively. Only FDA intake in g / day and% PV was not influenced by the inclusion of the SBL , all other nutrients ( DM, OM , CP, MM, NDF , and TDN ) decreased . The average daily gain ( ADG ) decreased with the inclusion of SBL and days on feed increased but feed conversion was not affected . The feed cost was reduced with the inclusion of the SBL . The replacement levels of 33 % and 66 showed better cost-benefit ratio , and the level of 66 % replacement of corn by SBL as indicated in the conditions of the present work .